The Contribution of Thomas Carlyle to British Idealism, c. 1880–1930. (October 2019) - Jordan, Alexander
Abstract : That the great Scottish man of letters Thomas Carlyle (1795–1881) exercised a formative influence over the 'British Idealism' of the late nineteenth and early twentieth centuries has long been noted by historians. However, this has been done so in passing, on the basis of a small fraction of the relevant source material. Through a close, comprehensive and sustained analysis of the entire corpus of relevant sources, the current article demonstrates that the British Idealists considered Carlyle to be far and away the most important British (Scottish) thinker of the nineteenth century, and considered themselves to be his heirs in almost every sense imaginable. Indeed, this is true of their theology, their ethics and their social and political thought.